The Relationship between Health Education and the Level of Knowledge of Adolescents About Reproductive Health - Tenny Tarnoto; Wita Oileri Tikirk; Asfila; Swarjana, I Kadek Dwi (Journal Kiara : Nursing and Midwifery, 2025)
Reproductive health has an important point in teenagers' lives but is often ignored. One of the impacts is experiencing sexually transmitted diseases. This triggers various serious health problems caused by teenagers' lack of knowledge about reproductive health. Research Objectives: To determine the relationship between health promotion and the level of knowledge of adolescents about reproductive health. This research method is quantitative with a pre-experimental research design and a one-group pre-posttest design. The sample in this study was 60 respondents according to the inclusion criteria. The sampling technique in this research uses a non-probability sampling method with a proportional sampling technique. The instrument used in this research is a questionnaire sheet taken from (Septiana, 2019) a booklet about reproductive health. This research uses SPSS Test Analysis. The results and analysis of the research show that before the Health Education was carried out there were 57 people with a presentation (95%) with a poor level of knowledge, after being given Health Education there was a significant increase of 40 people with a presentation (67%) with a good level of knowledge. With the average value, P.Value = 0.001 <0.005, it can be concluded that there is a relationship between Health Education and the level of knowledge of adolescents about reproductive health with a P-Value = 0.001.